To Delegate or Not to Delegate? Factors Influencing Human-Agentic IS Interaction - Strunk, Jobin Alexander; Banh, Leonardo; Nissen, Anika; Strobel, Gero; Smolnik, Stefan (Proceedings of the 45th International Conference on Information Systems (ICIS), 2024)
The evolution of information systems (IS) in recent years, driven by advancements such as AI-based digital assistants and autonomous vehicles, has fundamentally changed human-IS interaction. This transformation extends beyond mere user interaction to encompass the emergence of agentic IS, challenging traditional notions of human supervision. It prompts a reevaluation of IS research, with a focus on IS delegation as a new theoretical lens. However, research remains nascent, particularly in understanding the factors influencing delegation decisions. We compiled 26 articles and derived six key delegation mechanisms and their influencing factors, using grounded theory and co-occurrence analysis. We investigate attributes of human and the agentic IS, as well as task attributes and the delegation level that are relevant to the delegation mechanisms. Our research provides a nuanced understanding of factors influencing delegation decisions to agentic IS. We call for research considering the yet underrepresented but crucial interdependencies with a research agenda.